Instrumentos para el levantamiento de información de campo en competitividad y sostenibilidad para las empresas turísticas de alojamiento, ocio y recreación, del cantón Latacunga, provincia de Cotopaxi – Ecuador. - Hoyos Ramírez, Antony Marcelo (2023)
The present project focused on analyzing the instruments for the collection of field information on competitiveness and sustainability in lodging, leisure and recreation tourism enterprises in the canton of Latacunga, province of Cotopaxi, Ecuador. The objective of the research is to design an instrument that gathers information on competitiveness and sustainability in the Ecuadorian tourism context, in order to propose continuous improvement strategies for the companies. A bibliographic analysis and a characterization of existing instruments were carried out in order to identify the dimensions and subdimensions related to competitiveness and sustainability in the tourism sector. Based on this review, a single instrument was designed that integrates both variables with 30 items. To collect field information, quantitative and analytical approaches were applied, based on non-experimental designs. Subsequently, a pre-validation was carried out using the expert judgment methodology, obtaining a satisfactory result in terms of sufficiency, clarity, coherence and relevance, with a score of 42 out of 44. A pilot application was carried out in two hotels in Latacunga, unifying the results to establish the levels of acceptance of the instrument; it was established that the levels of acceptance of the instrument were 67.5%. In terms of competitiveness and 58.6% in relation to sustainability. The exploratory approach used in this research made it possible to explore and understand the variables of competitiveness and sustainability in the tourism sector of the canton of Latacunga, providing a solid basis for proposing continuous improvement strategies for the companies. However, a lack of acceptance by the business sector regarding the importance of competitiveness and sustainability aspects was identified. These results show the need to raise awareness and promote the implementation of sustainable practices and competitive strategies in the tourism sector in the area. In conclusion, this study contributes to the development of the tourism sector by providing a methodological tool to evaluate the competitiveness and sustainability of enterprises.